2013
DOI: 10.1063/1.4841315
|View full text |Cite
|
Sign up to set email alerts
|

Detailed energy distributions in laser-produced plasmas of solid gold and foam gold planar targets

Abstract: Foam gold was proposed to increase the laser to x-ray conversion efficiency due to its important applications. To understand the mechanism of x-ray enhancement, the detailed energy distributions and plasma profiles for laser-irradiated solid gold and foam gold targets were studied comparatively by hydrodynamic simulations using the code Multi-1D. It is confirmed that the radiation heat wave is subsonic for the normal solid gold target, while supersonic for the foam gold target. The shock wave, which is behind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…29,30 It was found that for the low-density foam gold target, the radiation ablation process is in the stage of supersonic heat wave and the shock wave behind the supersonic heat wave causes larger x-ray radiation emission and smaller kinetic energy loss. 36 Corresponding experiments which will be summarized in another paper have been performed to confirm its feasibility. It is of interest to combine the effect of high-Z mixture and that of low-density foam together for an added benefit.…”
Section: Simulations and Discussionmentioning
confidence: 96%
“…29,30 It was found that for the low-density foam gold target, the radiation ablation process is in the stage of supersonic heat wave and the shock wave behind the supersonic heat wave causes larger x-ray radiation emission and smaller kinetic energy loss. 36 Corresponding experiments which will be summarized in another paper have been performed to confirm its feasibility. It is of interest to combine the effect of high-Z mixture and that of low-density foam together for an added benefit.…”
Section: Simulations and Discussionmentioning
confidence: 96%
“…This is consistent with theoretical expectations. According to our previous studies, it was confirmed that the radiation heat wave is subsonic for the solid gold target, while supersonic for Au foam targets with initial density lower than 1 g cm −3 [26]. As to the Au foam targets, the shock wave behind the supersonic radiation heat wave produces an additional net outward radiation for the enhancement of the x-ray emission in the soft x-ray region.…”
Section: X-ray Spectramentioning
confidence: 71%
“…Efficient soft x-ray sources from laser-irradiated gold foam targets with well-controlled impurities than that of solid-density gold, [23] and previous simulations have demonstrated higher soft x-ray conversion efficiency from laser-irradiated high-Z foam targets [24][25][26]. The enhancement is theoretically caused by both the increase of the laser absorption and the reduction of ion kinetic energy for the low initial density.…”
Section: Nuclear Fusionmentioning
confidence: 87%
“…Over-critical foam generates a stronger soft x-ray compared with the solid material, which has been demonstrated in experiments using high-Z materials such as tantalum (Ta 2 O 5 ) [11] and gold [3,12]. Simulations have indicated that the kinetic energy is reduced in over-critical foam [13]. Experiments have demonstrated that the coronal plasma motion, which is the major contribution to kinetic energy, is mitigated in over-critical foam [14].…”
Section: Introductionmentioning
confidence: 83%